2017
DOI: 10.1212/wnl.0000000000004121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of patients with longstanding idiopathic REM sleep behavior disorder

Abstract: Prodromal PD markers are common in individuals with longstanding IRBD, suggesting that they are affected by an underlying neurodegenerative process. This observation may be useful for the design of disease-modifying trials to prevent PD onset in IRBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 37 publications
0
41
1
1
Order By: Relevance
“…22, 23 Patients diagnosed with neurogenic OH who also had REM sleep behavior disorder, anosmia and/or subtle motor signs were categorized as prodromal PD/DLB or prodromal MSA, since longitudinal studies have shown that they are already affected by an underlying CNS neurodegenerative disorder. 22, 24, 25 Since it was unclear at the time of testing whether these patients would ultimately transition into PD/DLB or MSA, they were excluded from the sub-group analysis in order to understand the impact of disease-specific lesions.…”
Section: Methodsmentioning
confidence: 99%
“…22, 23 Patients diagnosed with neurogenic OH who also had REM sleep behavior disorder, anosmia and/or subtle motor signs were categorized as prodromal PD/DLB or prodromal MSA, since longitudinal studies have shown that they are already affected by an underlying CNS neurodegenerative disorder. 22, 24, 25 Since it was unclear at the time of testing whether these patients would ultimately transition into PD/DLB or MSA, they were excluded from the sub-group analysis in order to understand the impact of disease-specific lesions.…”
Section: Methodsmentioning
confidence: 99%
“…36 Studies found that even long-term disease-free survivors had numerous clinical or biomarkers suggestive of ongoing neurodegeneration. 37,38 Prevalence of idiopathic RBD was finally estimated definitively in three population-based studies, all of which found a population prevalence of approximately 1%. [39][40][41] Because so many RBD patients develop PD (and DLB and MSA), RBD cohorts were used to directly measure other clinical prodromal markers.…”
Section: High-risk Cohorts Rise To the Forementioning
confidence: 99%
“…Rapid eye movement sleep behaviour disorder has been categorized into isolated RBD (iRBD) and secondary RBD [3], when associated with other neurological/neurodegenerative disorders [4][5][6], autoimmune diseases [7], or brainstem lesions [8]. Results from long-term follow-up studies [9], investigations in patients with long-standing iRBD [10], and studies evaluating biomarkers of synuclein-related neurodegeneration (including a-synuclein accumulation outside the central nervous system) [11,12], provided consistent evidence that iRBD is an early-phase asynucleinopathy, eventually evolving into Parkinson's disease, dementia with Lewy bodies or multiple system atrophy [13].…”
Section: Introductionmentioning
confidence: 99%